Small-sided games: An umbrella review of systematic reviews and meta-analyses - Clemente, F. M.; Afonso, J.; Sarmento, H. (PLOS ONE, 2021)
Objective: This umbrella review was conducted to summarize the evidence and qualify the methodological quality of SR and SRMA published on small-sided games in team ball sports.